Heteroatom doped carbon nanosheets from waste tires as electrode materials for electrocatalytic oxygen reduction reaction : effect of synthesis techniques on properties and activity - Veksha, Andrei (2021)
The effective method for synthesis of heteroatom doped carbon nanosheets (CNS) from waste tires was developed. The process employed NiO loaded CaCO₃ catalyst for catalytic chemical vapor deposition (CCVD) of the CNS from the non-condensable pyrolysis gas. The promotion of CaCO₃ with NiO had beneficial effect on carbon growth compared to pure CaCO₃, increasing the carbon yield by 2.8 and 8.0 times for the CCVD at 700 and 750 °C, respectively. On the contrary, the morphology and structure of synthesized S,O-doped CNS as well as oxygen reduction reaction (ORR) electrocatalytic activity were not influenced by the NiO addition. Based on the carbon yields and ORR electrocatalytic activities, the preferred CCVD temperature was 700–750 °C, resulting in the CNS with the ORR peak reduction potentials of −0.217 V to −0.220 V (versus −0.167 V for Pt electrode). The improvement of CCVD process was proposed decreasing the ORR peak reduction potential to −0.191 V. A mixture of NH₃ and H₂O was added to pyrolysis gas, promoting the development of mesoporosity and incorporation of N into the material structure. The developed technique is a viable solution for the conversion of non-condensable gases from tire pyrolysis into S,N,O-doped CNS for ORR.